Kampung Bersemi Jambon Gesikan: Pionir Aksi Iklim Kota Magelang Menuju Predikat Lestari Nasional - suwandoko; Rizza Arge Winanta; Adhi Surya Perdana (Politeknik Negeri Cilacap, 2026)
The Bersemi Jambon Gesikan Climate Village is a popular location for the climate village program in Magelang City. The initiative and nomination status upgrade from the main category to Sustainable. Obstacles faced included limited enrichment of climate change adaptation and mitigation activities, administrative procedures, and strengthening community institutions. Mentoring focused on increasing the capacity of administrators through socialization of the legal basis, administrative procedures, education on public awareness and participation, filling out the national climate change control registry system, preparing a five-year work program, and producing a profile video. Implementation methods included socialization and direct mentoring, so that administrators and community members could plan, implement, monitor, and periodically evaluate the program independently. The success of this activity included an increase in the assessment score for the climate village program category with a score of 91.07, the realization of sustainable adaptation and mitigation actions, institutional strengthening, the formation of a partnership network, and increased awareness of sustainable residential environments.